ORNAMENTAL VARIETIES OF GEDONG SONGO SEMARANG TEMPLE AS A TYPEFACE DESIGN INSPIRATION - Nugroho, Dany Prasetyo (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2019)
In the era of modernization, the language of visual communication has a significant development. Visual communication devices have changed and moved with process capabilities and speeds are constantly updated, thus providing the convenience as well as challenges for the user by using these facilities in a timely manner. The discipline of Typography has an important role in determining a success of the art form of communication. Unfortunately, this discipline received less attention in the world of graphic design in Indonesia. As the response, the writer in the study project entitled